Economic Factors Affecting the Cost of Living: A case study of State-Owned Commercial Bank’s staff in Luang Prabang City, Luang Prabang Province - PHONGSAVATH , Phetdamone; HOONGSENGPHA, Soudtida; INDAVONG, Dalounny; PHANLA , Phone; PHOTHITAY, Anousith (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
In the current global economic conditions and Lao PDR's economy encountered with gold prices fluctuations, Exchange rate fluctuations, Natural disasters and Epidemics especially COVID- Those problems have appeared to higher living costs for the people, which is a problem that the government attaches importance and improves solutions for a better quality of life of people. The objective of this study is: 1) the cost of living of staff for state-owned commercial banks in Luang Prabang, and 2) The economic factors affecting the cost of Living of staff for state-owned commercial banks in Luang Prabang by questioning and surveyed 88 staffs. The data was analyzed by the Pearson product moment correlation coefficient and stepwise multiple regression analysis. The study found that the cost of living of staff for state-owned commercial banks in Luang Prabang was is lower than their income, which shows that the quality of life of state-owned commercial bank employees is better living. The average monthly of cost of living are 4.056.425,07 kip per person, with pay yourself value 3,280,254.59 kip and others person paid 776.170,48 kip. The most costs of living comes from travel and communication expenses, education, housing rent, food and beverage expenses, personal expenses, entertainment and sports expenses, medical examinations and treatment expenses, respectively. The economic factors affecting the cost of Living of staff for state-owned commercial banks in Luang Prabang consist of two factors such as: 1) Changes in oil prices, 2) changes in the consumer price index had statistical significance at the level of 0,05. The part of Changes in interest rates and inflation do not affect the cost of living of for state-owned commercial banks in Luang Prabang.